Evaluation of Gayo coffee germplasm on Hypothenemus hampei (Coleoptera: Curculionidae) resistances. Issue 1 (January 2022) - Samsudin,; Dani,; Syafaruddin,
Abstract: The Gayo Experimental Station (GES) germplasm has the most complete collection of Arabica coffee in the world. The utilization of these collections to search coffee berry borer (CBB) resistant lines has not been carried out. This study aimed to evaluate 17 germplasm lines/varieties of Arabica coffee in GES against CBB resistance. Observation of CBB infestation level in the field was conducted at GES, Bener Meriah, Aceh. Each line used 10 trees and randomly selected 4 branches. Then the number of CBB-infested and healthy cherries were counted. At harvest time, were taken from each line 100 cherries randomly. Parameters observed were cherry weight, discus diameters, and cherries infested. Genetical resistance tests carried out at the plant protection laboratory of IIBCRI, Sukabumi, West Java. The parameter observed was the number of cherries infested. The results showed that CBB infestation level in germplasm was very low, caused by environmental factors that are not suitable for CBB development. There was a positive correlation between cherry discus diameters and CBB infestation rate. The results of genetic resistance testing in the laboratory showed that all of the evaluated Gayo arabica coffee lines/varieties showed a lightly susceptible response to CBB.